The effect of esteem support on rebound resilience during cycling time trials and an examination of potential mechanisms - McCluskey, T.; Stevens, M. (Sport, Exercise, and Performance Psychology, 2025)
Evidence suggests that social support can facilitate performance during sporting tasks and competition and boost resilience in the face of long-term sporting setbacks (e.g., injuries). Building on this, in an experiment, we examined whether social support helped people bounce back from an acute setback (i.e., demonstrate rebound resilience). Specifically, we tested the effect of esteem support on two objective indicators of rebound resilience: the distance participants traveled and their maximum heart rate in a cycling time trial after (relative to before) a setback. We also examined whether these effects were mediated by participants` within-task pain perceptions and retrospective evaluations of task motivation and challenge and threat appraisals. Participants (N = 80, 29 males, 51 females; M-age = 21.56 years, SD-age = 2.69 years) completed two time trials in quick succession. Following Trial 1, all participants received negative feedback about their performance, creating an opportunity for them to demonstrate rebound resilience by exerting themselves and striving to perform well during Trial 2. During Trial 2, participants either received (experimental group) or did not receive (control group) esteem support. Participants in the experimental group demonstrated greater increases in distance traveled and maximum heart rate compared to those in the control group during Trial 2 (i.e., greater rebound resilience). These effects were underpinned by increases in task motivation among those that received esteem support but not by challenge appraisals, threat appraisals, or perceived pain. Findings indicate that providing people with esteem support may be an effective way to enhance their capacity to bounce back from setbacks during sporting tasks.